Improving Mathematical Communication Ability and Self Regulation Learning Of Yunior High Students by Using Reciprocal Teaching - Abdul Qohar; Utari Sumarmo (Journal on Mathematics Education, 2013)
This paper presents the findings from a posttest experiment control group design  by  using reciprocal teaching, conducted  in Indonesia University of Education to investigate students’ ability in mathematical communication and self regulated learning.  Subject of the study were 254 of 9th grade students from three junior high schools of high, medium, and low level in Bojonegoro, East Java.  The instruments of the study were an essay mathematical communication test, and a self regulated learning scale. The study found that reciprocal teaching took the best role among school  cluster  and students’ prior mathematics ability on students’ mathematical communication ability and self regulated learning as well.  The other finding were there was interaction between school cluster and teaching approaches, but was no interaction between students’ prior mathematics ability and teaching approaches on mathematical communication ability and  self regulated learning. Moreover, there was association between mathematical communication and self regulated learning Keywords: Reciprocal Teaching, Mathematical Communication, Self Regulated Learning   DOI: http://dx.doi.org/10.22342/jme.4.1.562.59-74